2011
DOI: 10.1245/s10434-011-2071-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Esophageal Squamous Cell Carcinoma in Patients Positive for Human Epidermal Growth Factor Receptor Family Can Be Improved by Initial Chemotherapy with Docetaxel, Fluorouracil, and Cisplatin

Abstract: EGFR represents a predictor of postoperative recurrence and sensitivity to triple-drug combination therapy including a taxane. EGFR-positive patients may show improved prognosis with taxane combination chemotherapy and molecular targeted therapy for HER family members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…A multitude of studies have characterized the expression and significance of the HER family in ESCC [5-10]. EGFR and ErbB2 have been shown to be overexpressed in ESCCs compared to non-tumor tissues, and these proteins are important markers for the analysis of the prognosis and clinical course of the disease [5-8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multitude of studies have characterized the expression and significance of the HER family in ESCC [5-10]. EGFR and ErbB2 have been shown to be overexpressed in ESCCs compared to non-tumor tissues, and these proteins are important markers for the analysis of the prognosis and clinical course of the disease [5-8].…”
Section: Introductionmentioning
confidence: 99%
“…EGFR and ErbB2 have been shown to be overexpressed in ESCCs compared to non-tumor tissues, and these proteins are important markers for the analysis of the prognosis and clinical course of the disease [5-8]. ErbB3 is also up-regulated in ESCC and correlates with a clinical response to chemotherapy, but it has a limited prognostic value for survival in ESCC [9,10]. ErbB4 is frequently up-regulated in various cancer tissues [11-15], and experimental down-regulation of ErbB4 in different tumor cells suppresses growth [16-20].…”
Section: Introductionmentioning
confidence: 99%
“…NAC with taxane was recommended for ESCC patients with positive for HER family members. 31) These biomarkers will be candidates for the predictor of prognosis (recurrent risk) and choosing the therapeutic options. Molecular therapy targeting these biomarkers might improve the prognosis of esophageal cancer.…”
Section: New Therapeutic Strategy For Stage II Iii Esophageal Cancermentioning
confidence: 99%
“…The median survival time (MST) of all patients with T3–4M0 esophageal cancer who received CCRT was demonstrated to be only 16 months (5). Local recurrence and distant metastasis following definitive chemoradiation are the primary patterns of failure (6). Therefore, predicting the failure patterns and OS following CCRT is important.…”
Section: Introductionmentioning
confidence: 99%
“…However, identification of reliable markers predicting treatment outcome following CCRT remains limited in the previous literature (7). In the surgical groups of previous studies, epidermal growth factor receptor (EGFR) overexpression has been found in ESCC and may predict the postoperative recurrence and OS (6,810). The clinical importance of EGFR overexpression remains unsettled in ESCC patients undergoing CCRT (11).…”
Section: Introductionmentioning
confidence: 99%